2021
DOI: 10.1371/journal.pone.0259436
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of genes related to iron death in diabetic nephropathy through network and pathway levels based approaches

Abstract: Diabetic nephropathy is one of the common microvascular complications of diabetes. Iron death is a recently reported way of cell death. To explore the effects of iron death on diabetic nephropathy, iron death score of diabetic nephropathy was analyzed based on the network and pathway levels. Furthermore, markers related to iron death were screened. Using RNA-seq data of diabetic nephropathy, samples were clustered uniformly and the disease was classified. Differentially expressed gene analysis was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…In our study, Transcription factors HIF1A, KLF5, RUNX1, SP1, SPI1, STAT1, MBD1 and WT1 may be related to diabetic nephropathy. The results were similar to previous studies ( Hu et al, 2021 ). Chronic hyperglycemia can lead to microcirculatory disorders presenting with renal ischemia and hypoxia, and hypoxia can lead to inhibition of HIF-1α stability and function and decreased renal hypoxia tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, Transcription factors HIF1A, KLF5, RUNX1, SP1, SPI1, STAT1, MBD1 and WT1 may be related to diabetic nephropathy. The results were similar to previous studies ( Hu et al, 2021 ). Chronic hyperglycemia can lead to microcirculatory disorders presenting with renal ischemia and hypoxia, and hypoxia can lead to inhibition of HIF-1α stability and function and decreased renal hypoxia tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, this study used TRRUST V2 (www. grnpedia.org/) database to predict transcription factor (TF)-Gene (protein) interaction (Hu et al, 2021). Additionally, ubibrowser 2.0 (http://ubibrowser.ncpsb.org.cn/) was used to observe proteins involved in the ubiquitination process of target proteins.…”
Section: Target Gene Multi-factor Regulatory Analysismentioning
confidence: 99%
“…Recently, Hu et al reported that the vitamin D receptor (VDR) might be a transcription factor related to ferroptosis in DN. [14] Accumulating evidence has revealed the nephroprotective effect of VDR activation, including immune regulation, inflammatory inhibition and fibrosis alleviation. [15][16][17] Paricalcitol (PAR) is an active form of VD for the treatment of kidney diseases.…”
Section: Introductionmentioning
confidence: 99%